Microstructure, local electronic structure and optical behaviour of zinc ferrite thin films on glass substrate. Issue 10 (17th October 2018) - Singh, Jitendra Pal; Lee, Byeong-Hyeon; Lim, Weon Cheol; Shim, Cheol-Hwee; Lee, Jihye; Chae, Keun Hwa
Abstract : Zinc ferrite thin films were deposited using a radio-frequency-sputtering method on glass substrates. As-deposited films were annealed at 200°C for 1, 3 and 5 h, respectively. X-ray diffraction studies revealed the amorphous nature of as-grown and annealed films. Thickness of as-deposited film is 96 nm as determined from Rutherford backscattering spectroscopy which remains almost invariant with annealing. Transmission electron microscopic investigations envisaged a low degree of crystalline order in as-deposited and annealed films. Thicknesses estimated from these measurements were almost 62 nm. Roughness values of these films were almost 1–2 nm as determined from atomic force microscopy. X-ray reflectivity measurements further support the results obtained from TEM and AFM. Near-edge X-ray absorption fine structure measurements envisaged 3+ and 2+ valence states of Fe and Zn ions in these films. UV–Vis spectra of these films were characterized by a sharp absorption in the UV region. All films exhibited almost the same value of optical band gap within experimental error, which is close to 2.86 eV.